MUHAMMAD IBN ABDUL WAHHAB'S PERSPECTIVE ABOUT THE VERSES OF THE QUR'AN REGARDING THE SCIENCE OF THEOLOGY: موقف محمد ابن عبد الوهاب في آيات القرآن عن علم الكلام - Abdoulaye, Bamba; Rozy, Yahya Fathur (QiST: Journal of Quran and Tafseer Studies, 2024)
Since monotheism is the foundation of this religion and from it the entire religion proceeds, it received great attention from the scholars, both early and late, so each one of them turned to what he was most inclined to and they made significant contributions, and schools in it multiplied, each trying a different approach according to what he saw fit in the place where he lived. In it, and according to the conditions and needs of reality, Muhammad bin Abdul Wahhab was not an innovator among these contributions, and his interest in the science of monotheism was to liberate and purify it from all impurities and suspicions, and he did not delve into philosophical dialogues and theological differences, and in order to shed light on his approach, the importance of this came. The research is related to studying the sayings of this liberal and reformist figure and explaining the extent to which his approach in the science of monotheism relates to the science of theology. In writing this research, the researchers followed the inductive approach through the writings of Muhammad bin Abdul Wahhab and the analytical method to explain his ideas and opinions regarding theology and theological schools in the science of monotheism.